CT-Guided Cooled Radiofrequency Denervation for Chronic Arthritis Pain of the Hip and Shoulder - Sag, Alan Alper; Patel, Preet (Seminars in Interventional Radiology, 2022)
The paradigm in the treatment of arthritis pain is shifting for previously open surgical denervations of the hip and shoulder, as it already has for the geniculate nerves in knee arthritis. Interventional radiology is poised to contribute to this space with the use of CT guidance to provide safe, fast, and effective targeting of the target nerves for unequivocal diagnostic nerve block and definitive cooled radiofrequency denervation. The authors provide the background of which nerves are targeted for hip and shoulder denervation and the normal CT appearance of these blocks.
Keywords: interventional radiology; arthritis; pain management; analgesia; thermal ablation